Immersive storytelling and affective ethnography in virtual reality. Issue 1 (2nd January 2021) - Ceuterick, Maud; Ingraham, Chris
ABSTRACT: Virtual reality (VR) storytelling, particularly in its nonfictional modes, promises a sensory immersion among others whose lives and ways of being a privileged viewer might not otherwise experience. In this essay, by focusing on the Emmy-nominated 2018 VR film Traveling While Black, we explore how the immersive power of VR storytelling can enact ethnographic encounters premised less on the impulse to extract meaning from other people and their ways of life than on the sensory and affective force of being with others in an unfolding experience of both similitude and difference. Without wishing to overstate VR's empathy-inducing potential, we suggest that by situating viewers at a paradoxical threshold between proximity and distance, the affective power of VR derives in part from a narrative form capable of fostering nonappropriative relations.